The Effect Of Building Information Modeling (BIM) Skill For Construction Organization Achievement On The Success The Company - Ronny Durrotun Nasihien; Dika Yuniarsi (Journal of World Conference (JWC), 2020)
Optimizing the achievement of organizational / company goals is largely determined by effectiveness. More at this time in the AEC industry (Architecture, Engineering & Construction) the term BIM is often heard. That is a technology that in its development uses less time, labor and capital. This study aims to study whether it is necessary to develop BIM towards achieving a company's success. This study uses qualitative and quantitative methods. Respondents of the experimental study were 39 people. The data used are primary and secondary data obtained through observation, literature and questionnaires. Data analysis techniques with validity and reliability test. The results of the study show that expertise supported by BIM-based technology is against the achievement of company success, analysis shows valid and reliable results. This is also supported by type variables, which are adjusted to the qualifications needed by the company. The percentage obtained from the sex variable was 87.2%, female 12.8%. The conclusion of this study is that the higher the level of skills supported by gender variables, the success and achievement of the objectives of the work will increase. Suggestions for leaders to develop skills, especially for employees who have the potential and higher education in special sections to support better results.